OP0060-HPR Cross-Cultural Validation of The Systemic Sclerosis Quality of Life Questionnaire in Six European Countries: A Tool Validation Study. (15th July 2016) - Ndosi, M.; Alcacer-Pitarch, B.; Allanore, Y.; Del Galdo, F.; Frerix, M.; García Díaz, S.; Guidi, F.; Hesselstrand, R.; Kendall, C.; Matucci-Cerinic, M.; Müller-Ladner, U.; Sandqvist, G.; et al.
Abstract : Background: The Systemic Sclerosis Quality of Life (SScQoL) questionnaire is a 29-item tool developed in UK to measure needs-based patient-reported quality of life in people with systemic sclerosis (SSc). Objectives: To undertake a cross-cultural adaptation and validation of the SScQoL in six European countries. Methods: This was a cross-sectional study involving six European countries: Germany, France, Italy, Spain, Sweden and UK. Adult patients with a definite diagnosis of SSc, who were willing and able to complete the SScQoL were eligible. The English SScQoL was adapted into the five European languages using a forward-backward translation process. 1 The translated SScQoL was completed by patients and the data was analysed using Rasch models. Where local response dependency was evident, items were grouped into subscales (function, emotion, sleep, social and pain) and re-analysed to test the scaling properties and cross-cultural equivalence, thus allowing calibration of the SScQoL into an interval scale. Results: The adaptation of the SScQoL into European languages was seamless except in Germany, where patients reported problems in deciding yes/no responses for some items. Cross-cultural validation included 849 patients (mean age =57.9 years, SD =13.9), 87% of whom were women. All country-specific data except Germany had good fit to the Rasch model after correcting for local dependency. See table 1 . After excluding Germany from the analysis, the scale was validated and calibrated with cross-cultural adjustment for Italy in the social subscale. Conclusions: The SScQoL translated versions can be used as a valid common measure in France, Spain, Sweden, UK and Italy; the latter with adjustments in the social subscale. The German version requires further work. References: Beaton DE, et al. Guidelines for the process of cross-cultural adaptation of self-report measures. Spine. 2000;25(24):3186–91. Disclosure of Interest: None declared